Geographical differences in the management of metastatic de novo renal cell carcinoma in the era of immune-combinations - Porta, Camillo; Bamias, Aristotelis; Zakopoulou, Roubini; Myint, Zin W; Cavasin, Nicolò; Iacovelli, Roberto; Pichler, Martin; Kopecky, Jindrich; Kucharz, Jakub; Rizzo, Mimma; Galli, Luca; Büttner, Thomas; et al. (Minerva urology and nephrology, 2023)
BACKGROUND: The upfront treatment of metastatic renal cell carcinoma (mRCC) has been revolutionized by the introduction of immune-based combinations. The role of cytoreductive nephrectomy (CN) in these patients is still debated. The ARON-1 study (NCT05287464) was designed to globally analyze real-world data of mRCC patients receiving first-line immuno-oncology combinations. This sub-analysis is focused on the role of upfront or delayed partial or radical CN in three geographical areas (Western Europe, Eastern Europe, America/Asia). METHODS: We conducted a multicenter retrospective observational study in mRCC patients treated with first-line immune combinations from 55 centers in 19 countries. From 1152 patients in the ARON-1 dataset, we selected 651 patients with de novo mRCC. 255 patients (39%) had undergone CN, partial in 14% and radical in 86% of cases; 396 patients (61%) received first-line immune-combinations without previous nephrectomy. RESULTS: Median overall survival (OS) from the diagnosis of de novo mRCC was 41.6 months and not reached (NR) in the CN subgroup and 24.0 months in the no CN subgroup, respectively (P<0.001). Median OS from the start of first-line therapy was NR in patients who underwent CN and 22.4 months in the no CN subgroup (P<0.001). Patients who underwent CN reported longer OS compared to no CN in all the three geographical areas. CONCLUSIONS: No significant differences in terms of patients' outcome seem to clearly emerge, even if the rate CN and the choice of the type of first-line immune-based combination varies across the different Cancer Centers participating in the ARON-1 project.
Keywords: cytoredukční chirurgie; nádory ledvin; Carcinoma, Renal Cell; Cytoreduction Surgical Procedures; nefrektomie; lidé; retrospektivní studie; Retrospective Studies; Nephrectomy; Humans; Kidney Neoplasms; karcinom z renálních buněk